Chiral polypeptide hydrogels regulating local immune microenvironment and anti-tumor immune response - Junfeng Ding; Tianran Wang; Zhiqiang Lin; Zhenyu Li; Jiaxuan Yang; Fujiang Li; Yan Rong; Xuesi Chen; Chaoliang He (Nature Communications)
Abstract The impact of chirality on immune response has attracted great interest in cancer vaccine research recently. However, the study of chiral synthetic polypeptide hydrogels as cancer vaccines as well as of the impact of biomaterials themselves for antitumor immunotherapy has rarely been reported. Here, we show the key role of residue chirality of polypeptide hydrogels in antitumor immunity and local immune microenvironment regulation. Compared to poly(γ-ethyl-L-glutamate)-based hydrogels (L-Gel), poly(γ-ethyl-D-glutamate)-based hydrogels (D-Gel) induces enhanced level of immune cell infiltration. However, D-Gel causes higher levels of suppressive markers on antigen-presenting cells and even induces stronger T cell exhaustion than L-Gel. Finally, D-Gel establishes a local chronic inflammatory and immunosuppressive microenvironment and shows insufficient anti-tumor effects. Conversely, the milder host immune responses induced by L-Gel leads to more effective tumor inhibition. This study provides insights on the role of residue chirality in the regulation of local immune microenvironment and affecting antitumor immune response.